On parameter estimation in the bass model by nonlinear least squares fitting the adoption curve - Marković, Darija; Jukić, Dragan (Zielona Góra: Uniwersytet Zielonogórski)
The Bass model is one of the most well-known and widely used first-purchase diffusion models in marketing research. Estimation of its parameters has been approached in the literature by various techniques. In this paper, we consider the parameter estimation approach for the Bass model based on nonlinear weighted least squares fitting of its derivative known as the adoption curve.
Keywords: Bass model; least squares estimate; existence problem; data fitting